2008
DOI: 10.1007/s10532-008-9186-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of methyl parathion hydrolase and its application in detoxification of organophosphates

Abstract: The coding region of mpd gene corresponding to mature methyl parathion hydrolase (MPH) was heterologously overexpressed in Escherichia coli BL21 (DE3) by using pET expression system. The lactose-induced expression yield of MPH is increased 2-fold compared with IPTG as inducer. Furthermore, it was found that specific activity of MPH increased 48% by reducing the induction temperature to 22 degrees C. The addition of 25 mM lactose at 22 degrees C, the MPH activity of fermentation broth had a specific activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 19 publications
(24 reference statements)
0
25
1
Order By: Relevance
“…were able to degrade fenitrothion over a temperature range of 20-40°C with optimum degradation at 30°C. Yang et al (2008) showed that 30°C is the optimal temperature for heterologous expression of methyl parathion hydrolase enzyme (MPH). They found that 30°C is optimal for the formation of properly folded enzyme and inhibition of ATP-dependent and ATPindependent proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…were able to degrade fenitrothion over a temperature range of 20-40°C with optimum degradation at 30°C. Yang et al (2008) showed that 30°C is the optimal temperature for heterologous expression of methyl parathion hydrolase enzyme (MPH). They found that 30°C is optimal for the formation of properly folded enzyme and inhibition of ATP-dependent and ATPindependent proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…YC-1 (Yang et al 2008), and lactic acid bacteria ). Degradation of organophosphorus pesticides by cultured microorganisms, even at high pesticide concentration, has been reported previously (Liu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Soil bacteria capable of degrading organochlorinated pesticides have also been reported (Hussain et al 2007;Raina et al 2008;Goswami and Singh 2009). The gene encoding chlorpyrifos or organophosphorus pesticide degrading enzyme was isolated previously (Fu et al 2004;Liu et al 2005;Zhang et al 2006;Yang et al 2008;Cho et al 2009), but this work is the first report of a gene encoding a TCP degrading enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphorus hydrolases (OPH) play important roles in the decontamination of organophosphate pesticides and are useful in the bioremediation of pollution caused by organophosphate pesticides (Dong et al 2005;Yang et al 2008Yang et al , 2010Chu et al 2006Chu et al , 2010Xiao et al 2008). A methyl parathion hydrolase, Ochr-MPH, isolated from Ochrobactrum sp.…”
Section: Introductionmentioning
confidence: 99%